Hydrogen Sulfide Reverses Aging-Associated Amygdalar Synaptic Plasticity and Fear Memory Deficits in Rats - Zhan, Jin-Qiong; Zheng, Li-Li; Chen, Hai-Bo; Yu, Bin; Wang, Wei; Wang, Ting; Ruan, Bo; Pan, Bin-Xing; Chen, Juan-Ru; Li, Xue-Fen; Wei, Bo; Yang, Yuan-Jian (Frontiers in Neuroscience, 2018)
As an endogenous neuromodulator, hydrogen sulfide (H2S) exerts multiple biological effects in the brain. Previous studies have shown that H2S is involved in the regulation of neural synaptic plasticity and cognition in healthy rodents. It is well known that there is a progressive decline of cognitive function that occurs with increased age. The purpose of this study was to investigate the role of H2S in aging-associated amygdalar synaptic plasticity and cued fear memory deficits as well as to explore the underlying mechanisms. We found that H2S levels in the amygdala were significantly lower in aged rats when compared with healthy adult rates, which displayed significant deficits in long-term potentiation (LTP) in the thalamo-lateral amygdala (LA) pathway and amygdala-dependent cued fear memory. Bath application of an H2S donor, sodium hydrogen sulfide (NaHS), significantly reversed the impaired LTP in brain slices from aged rats, and intra-LA infusion of NaHS restored the cued fear memory in aged rats. Mechanismly, we found that H2S treatment significantly enhanced NMDAR-mediated synaptic responses in the thalamo-LA pathway of aged rats. Notably, GluN2B-containing NMDARs, but not GluN2A-containing NMDARs, contributed to the effects of H2S on aging-associated impairments of amygdalar LTP and fear memory, because applying GluN2B antagonist could abolish the beneficial effects of NaHS treatment on amygdalar LTP and cognitive performance in aged rats. Collectively, these results show that H2S can reverse aging-associated amygdalar synaptic plasticity and fear memory deficits by restoring the function of GluN2B-containing NMDARs, suggesting that supplement of H2S might be a therapeutic approach for aging-related cognitive disorders.